Budaya Kekerasan dan Pendidikan Multikultural di Sekolah: Sebuah Telaah Kritis - Anju Nofarof Hasudungan (Keguruan, 2022)
This study aims to analyze the culture of violence and multicultural education in schools which are critically examined. That, violence is not justified in life at school. Especially if violence is justified because of the differences between students in terms of religion, ethnicity, race and class. This study uses descriptive qualitative research methods.  Data collection is done through observation, document analysis and literature study. In Indonesia, the implementation of the multicultural education paradigm is implicit in Law no. 20 of 2003 concerning the National Education System it is stated that education is carried out in a democratic, fair, non-discriminatory manner, upholding human rights, religious values, cultural values and national pluralism; Education is organized as a systemic unit with an open and multi-meaning system. This means that schools and history learning can play a role in the development of multicultural education as an effort to prevent violence in schools.